2009
DOI: 10.1007/s10646-009-0450-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrated assessment of water quality of the Costa da Morte (Galicia, NW Spain) by means of mussel chemical, biochemical and physiological parameters

Abstract: The aim of this study was to assess environmental quality at some of the sites most severely affected by the Prestige oil spill off 2 years after the spillage (April and November 2004). For this purpose analyses of polycyclic aromatic hydrocarbons (PAH) and several biochemical (antioxidant enzymes catalase, glutathione reductase, glutathione peroxidase, superoxide dismutase and DT-diaphorase and lipid peroxidation) and physiological [scope for growth (SFG)] biomarkers were determined on wild mussel populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 95 publications
1
5
0
Order By: Relevance
“…In addition, levels of induction returned to baseline over a time period of 2 years at most sites (Martinez‐Gomez et al ). Two years after the spill, PAH concentrations were returning to background, but some sites still had a spill signature (Fernandez et al ). To determine whether these concentrations of PAHs were having any biological effect, a variety of effects biomarkers were measured in mussels along a spatial gradient.…”
Section: Determining the Spatial And Temporal Extent Of Contaminationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, levels of induction returned to baseline over a time period of 2 years at most sites (Martinez‐Gomez et al ). Two years after the spill, PAH concentrations were returning to background, but some sites still had a spill signature (Fernandez et al ). To determine whether these concentrations of PAHs were having any biological effect, a variety of effects biomarkers were measured in mussels along a spatial gradient.…”
Section: Determining the Spatial And Temporal Extent Of Contaminationmentioning
confidence: 99%
“…To determine whether these concentrations of PAHs were having any biological effect, a variety of effects biomarkers were measured in mussels along a spatial gradient. At the spill sites, mussels had elevated oxidative stress markers but no change in physiological markers that indicate changes in growth and reproductive capacity (Fernandez et al ). Taken together, these data indicated that exposure to oil from the Prestige may have had an impact on fish health after the spill but with a return to a normal physiological status within a few years.…”
Section: Determining the Spatial And Temporal Extent Of Contaminationmentioning
confidence: 99%
“…The measurement of the activity of antioxidant enzymes in mussels has been widely used as biomarkers of exposure to environmental pollutants (Lam, 2009). For the present study, we selected some exposure biomarkers (Catalase -CAT, Glutathione Reductase -GR and Glutathione S-tranferase -GST activities) and an effect biomarker (Lipid peroxidation -LPO), which have been used to reveal the exposure to metals and a wide range of organic compounds in the environment (Campillo et al, 2013;Fernández et al, 2010aFernández et al, , 2010bFernández et al, , 2012Fitzpatrick et al, 1997;Funes et al, 2006;Lee et al, 1988;Regoli, 1998;Vidal-Liñán et al, 2010). CAT is an extremely active catalyst for reduction of H 2 O 2 to H 2 O at high levels of H 2 O 2 , but at low levels it modulates the detoxification of other substances as phenols and alcohols through reactions coupled to the H 2 O 2 reduction.…”
Section: Introductionmentioning
confidence: 99%
“…The 4 presence of contaminants in the marine environment alters this energy balance, making SFG a marker for 5 toxic stress. SFG has been successfully applied in programmes monitoring chronic pollution (Albentosa 6 et al, 2012;Cotou et al, 2002;Halldorsson et al, 2005;Toro et al, 2003a;Widdows et al, 1995;7 Widdows et al, 2002), acute pollution associated with a spill (Fernández et al, 2010b ;Larretxea and 8 Pérez Camacho, 1995) and in laboratory contaminant exposure studies (Kraak et al;1997, Sobral and9 Widdows, 1997; Wang and Chow, 2002;Widdows and Page, 1993). 10 Different studies have shown the usefulness of marine clams as sentinel organisms for the detection of 11 the impact of environmental pollution in coastal waters through the application of different biomarkers 12 (Bebianno et al, 2004;Nasci et al, 1999Nasci et al, , 2000.…”
Section: Introductionmentioning
confidence: 99%